Uncovering Barriers on Project Based Learning in Merdeka Curriculum - Roberts, Jasmine Angelique; Nurkhamidah, Neni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The implementation of Project Based Learning (PBL) in English subjects is in line with Merdeka Curriculum because students can learn by actively engaging in real-world and personally meaningful projects. This study aims to find out the student challenges that hinder their engagement in English Project Based Learning and find out the roles of teacher that faced by students in overcoming barriers in English Project Based Learning on Merdeka Curriculum. This research uses a qualitative approach with a descriptive approach. The research was conducted at SMPN 189 Jakarta. Data was collected through questionnaires and interviews to identify barriers to student engagement and the role of teachers in overcoming those barriers. A total of 59 students participated as respondents for the questionnaire method and 2 teachers of United Kingdom subjects were interviewed. This study used the Likert scale to calculate the results of the questionnaire and to analyze the data from the interviews used transcription and highlighting of the results points. Data analysis involves transcription and analysis of interview responses to draw overall conclusions. The findings of this study highlight the difficulties in collaboration, project planning and execution, time, and motivation with engagement. Teachers act as facilitators, creating a supportive environment, emphasizing personal connections, and using a variety of feedback strategies to ensure inclusive participation and improve the quality of learning